Looking at the Link between Study Habits and Academic Achievement: The Case of Indonesian EFL Student Teachers - LENNY MARZULINA; DIAN ERLINA; NOVA LINGGA PITALOKA; FLORENSIA ANGGARDE PARAMIKA (Indonesian Research Journal in Education |IRJE|, 2019)
The purpose of this study was to look at the link between English as a foreign language (EFL) student teachers’ study habits and academic achievement. A questionnaire of study habits inventory (SHI) and students’ cumulative GPAs were used as research instruments to EFL student teachers in one English education study program at an Indonesian state Islamic university. Data were analyzed through using the descriptive statistics and Pearson Product Moment Correlation. In general, it was found that EFL student teachers’ habits significantly correlated with their academic achievement. Also, the results of the linear regression analysis showed that EFL student teachers’ study habits led to their academic achievement. The findings of this study indicated that the correlation between study habits and academic achievement existed. In the context of learning English in a non-English speaking country like Indonesia, this study provides information for researchers and teacher educators to understand how the link between study habits and academic achievement is significantly correlated each other.